Psychometric evaluation of the translated arabic version of the geriatrics health behavior questionnaire (GHBQ) for geriatric nurses: a cross-sectional study - Mostafa shaban; Huda Hamdy Mohammed; Fatma Gomaa Mohamed Amer; Hla Hossni Elsayed; Sayed Ibrahim Ali; Ateya Megahed Ibrahim (BMC, 2024)
Abstract Background The Geriatrics Health Behavior Questionnaire (GHBQ) is essential for assessing health-related behaviors among older adults populations. This study focuses on the translation, cultural adaptation, and psychometric evaluation of the Arabic version of the GHBQ to ensure its relevance and accuracy for Arabic-speaking older adults individuals. Methods This cross-sectional study was conducted at the Cairo University Educational Hospital's outpatient clinic. The GHBQ was translated and culturally adapted through a systematic process, including initial translation, back-translation, expert review, and pilot testing. The psychometric properties of the Arabic-translated GHBQ were evaluated using a sample of 200 older adults Arabic-speaking participants. Reliability was assessed using Cronbach's alpha (α) and Intraclass Correlation Coefficient (ICC). Validity was evaluated through Content Validity Index (CVI), Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). Results The Arabic GHBQ demonstrated excellent reliability with Cronbach's alpha values ranging from 0.74 to 0.87 across subscales and ICC values confirming reproducibility (ICC = 0.82). The CVI indicated strong content validity (average CVI = 0.91). EFA revealed a five-factor structure, explaining 72% of the variance, with all factor loadings exceeding 0.60. CFA supported the questionnaire's structure with fit indices meeting recommended criteria: χ²/df = 2.05, NFI = 0.92, TLI = 0.94, GFI = 0.90, SRMR = 0.05, AIC = 140.35, and BIC = 160.22. Criterion validity was confirmed through significant correlations with established health behavior measures (r = 0.63, p < 0.001). Conclusions The culturally adapted Arabic version of the GHBQ is a reliable and valid tool for assessing health behaviors in the older adults population in Egypt. This instrument can aid healthcare providers in identifying and addressing health behaviors, ultimately improving the well-being of this demographic. Future research should focus on expanding the sample and comparing the GHBQ with other similar tools used in Arabic-speaking populations.